HISTORY OF THE FIGHT AGAINST INFECTIOUS DISEASES IN THE UZBEK SSR AND ITS RESULTS (1941-1945) - Turayev Muradulla (Western European Studies, 2024)
A significant portion of Uzbekistan's rural population has been exposed to the harmful effects of toxic chemical substances over many years. Violations of regulations on the use of hazardous substances in agriculture have annually resulted in numerous cases of poisoning among the population of the republic. The amount of chemical substances applied to agricultural lands in the republic has been increasing year by year.
Keywords: medical cadre; doctors; general practitioners